Phenomenology as transcendental empiricism - Kebuladze, Vahtang (Actual Problems of Mind, 2017)
The author formulates the foundational principles of a phenomenological theory of experience, which he calls «transcendental empiricism». Based of these principles he describes various levels of a phenomenological investigation of experience which are hierarchically organized.